The influence of Vygotsky in Movimento da Escola Moderna Early Childhood Education Curriculum - Folque, Maria da Assunção (2012)
The Movimento da Escola Moderna (MEM) - Modern school movement concerns all levels of education. It is the result of the cooperative work of teachers in Portugal over the course of thirty years. Sérgio Niza is one of its founders and educational leaders. This paper will discuss the formative aims proposed by the MEM Early Childhood Model and the philosophical foundations of practices applied to early childhood classrooms, and highlights how Vygotsky’s theory of development and learning is one of its major theoretical foundations.